f(2)=2(2)+3

Simple and best practice solution for f(2)=2(2)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(2)=2(2)+3 equation:


Simplifying
f(2) = 2(2) + 3

Reorder the terms for easier multiplication:
2f = 2(2) + 3

Multiply 2 * 2
2f = 4 + 3

Combine like terms: 4 + 3 = 7
2f = 7

Solving
2f = 7

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '2'.
f = 3.5

Simplifying
f = 3.5

See similar equations:

| 5[3x-4]=8[x+2]+5 | | 45.2-5h=2.8 | | -2(5-8)+6*5= | | 20=-6(-9-3x) | | 3x-2(5-x)=5(x-2) | | (x-1)(2x+6)=104 | | 7(-8m+2)=-434 | | 4=-(x-7)+3 | | 21dy+6xy-6xv-21dv= | | 8x+(-5)=35 | | Y=1.03x | | 2y+3y+30+4x-100+x+5=360 | | f(1)=1(1)+3 | | vw+uw=uv | | 2x+(x+6)=54 | | -2a-6a=24 | | (w^2-4w+7)+(3w^2+5w-3)= | | 2y-36x=45-38y | | 1350=45x+30y | | 10=8-4y | | 3x*ln(x+3)+4=0 | | 11w+2(3w-1)=5 | | (9y-6)(1.5)+3.5y= | | 3.50x+40=57.50 | | 7n+n=64 | | 30x^2-25x=0 | | 2(2x+3)=24 | | -2c-24=2c-12 | | 9u-5u=36 | | 5x+2=-5 | | 6-3x=14x+2 | | 13=7r-6-2 |

Equations solver categories